Основные результаты комплексных исследований ЮгНИРО в Азово-Черноморском бассейне и Мировом океане в 1995 году - Gubanov, E.P.; Southern Scientific Research Institute of Marine Fisheries and Oceanography (YugNIRO) (YugNIRO, 1996)
Results of YugNIRO complex researches are presented and assessment of the state and prospects of development for Ukrainian fisheries in international legal aspect is given. Main results of oceanographic researches, problems of ctenophore Mnemiopsis development dynamics, problems of biology and stock assessment of commercial target species in the Azov-Black Sea area and in the Indian Ocean as well as problems of exploration of fishing areas in the North-Eastern Atlantic are considered. Prospects of production of new medicinal prophylactic preparations made of Black Sea seaweeds are revealed. Conception of development of fisheries in the Crimea is offered. Представлены результаты комплексных исследований ЮгНИРО, дана оценка состояния и перспектив развития рыболовства Украины в международно-правовом аспекте. Рассмотрены основные итоги океанографических исследований, вопросы динамики развития гребневика мнемиопсиса, биологии и оценки запасов промысловых объектов Азово-Черноморского бассейна и Индийского океана и освоения промыслом районов Северо-Восточной Атлантики. Показаны перспективы получения новых лечебно-профилактических препаратов из черноморских водорослей. Представлена концепция развития рыбного хозяйства Крыма. Published